Development of the Hajj Savings Mechanism with the Wadi'ah Agreement on BSI Surabaya Basuki Rahmat - Zinah, Fitriyatus; Rohmah, Nuzulur; Kunaifi``, Aang (Danadyaksa: Post Modern Economy Journal, 2024)
This study proposes and analyzes the development of a Hajj savings mechanism based on the principles of the Wadi'ah Agreement. Using a comprehensive literature review and comparative analysis, the study outlines specific implementation steps to enhance the effectiveness and sustainability of the Hajj savings program. Existing mechanisms for Hajj savings face challenges, such as a lack of transparency in profit distribution and sustainability issues. This research introduces a novel framework utilizing the principles of the Wadi'ah Agreement to address these challenges, aiming to improve fairness and efficiency in managing Hajj savings funds. The study's contributions highlight a distinct departure from conventional systems, providing a practical roadmap for integrating the new framework into existing financial structures.